The extent of job satisfaction for employees of the School Health Affairs Department in the General Administration of Education in Taif Governorate, and its relationship to some variables - Al-Salami, Suleiman Hammoud Sweimel; Al-Hashibri, Mutaib Hashim (Journal of Educational and Psychological Sciences, 2022)
The educational supervisor is one of the elements of the educational process and is affected by many variables and material conditions and morale at work, and accordingly changes their production positively or negatively. It is a scientific fact that job satisfaction and being convinced of it pushes the individual to make maximum efforts to achieve it. Job satisfaction is a motive for achievement and vice versa. Hence, the importance of identifying what affects the satisfaction of educational supervisors, and the positive and negative reactions in the field of supervisory work. Therefore, this study mainly aimed to identify the level of job satisfaction for employees of the School Health Affairs Department in the General Administration of Education in Taif Governorate. The descriptive survey method was used to determine the extent of job satisfaction, and the questionnaire was built based on the theoretical framework of the study, and previous studies. The study reached several results, the most important of which are: There are no statistically significant differences at the level (α ≤ 0.05) between the average ranks of the two groups in the level of satisfaction according to the variables of gender, educational qualification, years of experience, and the job position. Therefore, the study recommended paying attention to the level of job satisfaction among the employees of the School Health Affairs Department in Taif education by conducting programs and training courses for them that include how to deal with colleagues and superiors, work tasks and duties, appreciation and self-respect.